TANTANGAN DAKWAH DI ERA POSMODERNISME - Munfarida, Elya (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
As a criticism to modemism, posmodemism has created new cultural realities different from the previous. Through its political acts and strategies, postmodernism has constructed cultural hypereality and complexity. This change becomes a chance and also threat that we need to be critical to anticipate the negative effects. One of its strategies is cultural deconstruction, which denies transcendental signs, meanings, and values, represents one of its negative effects. It will eliminate religious values which by contrast place transcendental values as its principle. For that reason, we need to contextualize Islamic teachings in order not to make postmodernism eliminate Muslims’ sense of religiousity. Da’wa, as a means of communication and transformation of Islamic values, plays a significantrole in this postmodernism era. Consequently, reconstruction of contextual da’wa strategy should be committed to balance the domination of postmodernism cultures.